Impact of Fe3O4, CuO and Al2O3 on the AC breakdown voltage of palm oil and coconut oil in the presence of CTAB - Mohamad N.A.; Azis N.; Jasni J.; Kadir M.Z.A.A.; Yunus R.; Yaakub Z. (MDPI AG, 2023)
Alumina; Aluminum oxide; Bleaching; Cleaning; Copper oxides; Electric breakdown; Iron oxides; Magnetite; Nanofluidics; Nanoparticles; Petroleum refining; Surface active agents; Transmission electron microscopy; Weibull distribution; AC breakdowns; Al2O3; Coconut oil; Fe3O4; Nanofluids; Palm oil